Synergistic effect of graphene and multi-walled carbon nanotubes composite supported Pd nanocubes on enhancing catalytic activity for electro-oxidation of formic acid. Issue 13 (25th February 2016) - Yousaf, Ammar Bin; Imran, M.; Zeb, Akif; Xie, Xiao; Liang, Kuang; Zhou, Xiao; Yuan, Cheng-Zong; Xu, An-Wu
Abstract : Synergistic effect of rGO/MWCNTs composite supported Pd nanocubes enhanced the performance of direct formic acid fuel cells. Abstract : The selectivity and sensitivity of a support material can highly improve the catalytic performance of known catalysts. As an excellent electron transfer material and having intercalation characteristics, reduced graphene oxide/multiwalled carbon nanotubes (rGO/MWCNTs) composite provides a synergistic effect on enhancing the electrocatalytic performance of direct formic acid fuel cells. Herein, we report the synthesis of palladium nanocubes (NCs) supported on rGO/MWCNTs composite, rGO and MWCNTs. The electrocatalytic performance for the formic acid oxidation reaction (FAOR) is tested by detailed electrochemical techniques such as cyclic voltametry (CV), chronoamperometery (CA) and electrochemical impedence spectroscopy (EIS) for all supported Pd-NCs catalysts and the results were compared with unsupported Pd-NCs. A significant, systematic and desired improvement in the activity of the FAOR is found for the Pd-NCs/rGO/MWCNTs catalyst. The order of activity is observed to be Pd-NCs < Pd-NCs/MWCNTs < Pd-NCs/rGO < Pd-NCs/rGO/MWCNTs. The results can be attributed to the synergistic effect induced by the hybrid support material on enhancing the activity of the Pd-NCs catalyst.